Position and Implications of the Judge's Pardon Decision (Rechterlijk Pardon) in the Criminal Code System and the New Criminal Code: A Normative Study Based on SEMA Number 1 of 2026 - Bebly Rajes Punjabi Bebly; Kholidazia El Hamzah F; Muhamad Dluha; Achmad Syamsul Askandar (UNIVERSITAS PAKUAN, 2026)
The evolution of Indonesian criminal law reflects a significant paradigm shift in sentencing, transitioning from a retributive framework toward a more humane and substantive justice-oriented approach. A pivotal manifestation of this reform is the codification of judicial pardon (Rechterlijk Pardon) under Law Number 1 of 2023 on the Criminal Code (KUHP), which empowers judges to withhold criminal sanctions from a defendant proven guilty, subject to specific equitable considerations. This study aims to analyze the legal standing of Rechterlijk Pardon within the sentencing architecture of the new Criminal Code (KUHP) and the new Criminal Procedure Code (KUHAP), examine its regulatory framework and application under Supreme Court Circular (SEMA) Number 1 of 2026, and assess its juridical implications for the overarching objectives of punishment. Employing a normative legal research methodology, this study utilizes statutory, conceptual, and case-based approaches. The findings indicate that Rechterlijk Pardon serves as an instrument of sentencing flexibility that reinforces the realization of substantive justice. The novelty of this research lies in its critical analysis of the interplay between the normative provisions of the new KUHP and their operationalization through SEMA Number 1 of 2026, which serves to circumscribe judicial discretion while ensuring systemic consistency across the national criminal justice apparatus. Keywords: Judicial Pardon (Rechterlijk Pardon), Criminal Law, New Penal Code, New Criminal Procedure Code.